2019
DOI: 10.2147/ott.s218308
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA EGOT Promotes the Malignant Phenotypes of Hepatocellular Carcinoma Cells and Increases the Expression of HMGA2 via Down-Regulating miR-33a-5p</p>

Abstract: Background: Chronic hepatitis C virus (HCV) infection is an important risk factor for hepatocellular carcinoma (HCC). EGOT is a long non-coding RNA (lncRNA) induced after HCV infection that increases viral replication by antagonizing the antiviral response. Interestingly, EGOTalso acts as a crucial regulator in multiple cancers. However, its role in HCC remains unclear. Methods: Real-time PCR (RT-PCR) was used to detect the expression of EGOT in HCC samples and cell lines. CCK-8 assay and colony formation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…13 Some studies revealed that miR-33a-5p regulated metastasis and apoptosis in various cancers. 14,15 However, there are few studies on the regulation of GC mediated by miR-33a-5p. Cyclin-dependent kinases 7 (CDK7) mainly takes part in Pol II transcription process by acting as enzymatic cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some studies revealed that miR-33a-5p regulated metastasis and apoptosis in various cancers. 14,15 However, there are few studies on the regulation of GC mediated by miR-33a-5p. Cyclin-dependent kinases 7 (CDK7) mainly takes part in Pol II transcription process by acting as enzymatic cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low miR-33a expression is associated with a low survival rate in patients with hepatocellular carcinoma (33). Similarly, Wu et al (34) and Han et al (35) have illustrated that lncRNA eosinophil granule ontogeny transcript and lncRNA colorectal neoplasia differentially expressed in hepatoma cells inhibit miR-33a expression, which upregulates the target gene high mobility group AT-hook 2 (HMGA2), thereby promoting the proliferation, migration, invasion and chemoresistance of hepatoma cells (Fig. 1E).…”
Section: Mir-33a and Its Role In Cancermentioning
confidence: 72%
“…Studies by H, L, et al [20]demonstrated that the long-chain non-coding RNA HIF1A-AS2 was overexpressed in osteosarcoma tissues and cells, which could interact with miR-33b-5p and negatively regulate its expression, thereby up-regulating the expression of the target protein SIRT6 of miR-33b-5p. Studies by S, W et al [21]showed that the expression of long-chain non-coding RNA EGOT in hepatocellular carcinoma (HCC) tissues was signi cantly up-regulated. EGOT has a signi cant regulatory effect on the survival, migration and invasion of liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%